2011
DOI: 10.1590/s1807-55092011000400011
|View full text |Cite
|
Sign up to set email alerts
|

"Feedback" após boas versus más tentativas melhora a aprendizagem motora em crianças

Abstract: O presente estudo investigou se a aprendizagem motora de crianças pode ser beneficiada pelo "feedback" (conhecimento de resultados -CR) fornecido após tentativas relativamente boas de prática, ao invés de após tentativas ruins. A tarefa requeriu que os participantes arremessassem saquinhos de feijão em um alvo circular fixo, posicionado no chão, a uma distância de 3 m. Vinte e oito crianças do ensino fundamental (idade média: 10,6 anos) participaram deste experimento. A fase de prática consistiu de 10 blocos d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Regardless, to our knowledge, this is the first study to report intrinsic motivation and augmented feedback processing, when considered together, predict a measure of motor learning. One other study showed evidence that intrinsic motivation predicted motor learning (Saemi et al, 2011), but this study did not consider augmented feedback processing; and two other studies showed evidence augmented feedback processing predicted motor learning (Luft et al, 2013(Luft et al, , 2014, but these studies did not consider intrinsic motivation. Interestingly, intrinsic motivation and augmented feedback processing were not significantly correlated, suggesting that individuals who are more intrinsically motivated to learn do not necessarily engage in greater augmented feedback processing while learning.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Regardless, to our knowledge, this is the first study to report intrinsic motivation and augmented feedback processing, when considered together, predict a measure of motor learning. One other study showed evidence that intrinsic motivation predicted motor learning (Saemi et al, 2011), but this study did not consider augmented feedback processing; and two other studies showed evidence augmented feedback processing predicted motor learning (Luft et al, 2013(Luft et al, , 2014, but these studies did not consider intrinsic motivation. Interestingly, intrinsic motivation and augmented feedback processing were not significantly correlated, suggesting that individuals who are more intrinsically motivated to learn do not necessarily engage in greater augmented feedback processing while learning.…”
Section: Discussionmentioning
confidence: 93%
“…One speculation is self-control participants are more intrinsically motivated during the acquisition phase (Sanli et al, 2013;Wulf, 2007), and intrinsic motivation is associated with enhanced motor learning (Saemi, Wulf, Varzaneh, & Zarghami, 2011). Self-control participants are theorized to be more intrinsically motivated because they likely have higher perceived autonomy, which is positively associated with intrinsic motivation (Banack, Sabiston, & Bloom, 2011;Black & Deci, 2000;Jõesaar, Hein, & Hagger, 2012).…”
Section: Self-controlled Feedback and Intrinsic Motivationmentioning
confidence: 99%
“…According to the guidance hypothesis, the low frequency of the feedback and feedback after poor trials with large errors when the learner is directed towards the correct movement pattern is considered to be more effective than feedback after good trials and small errors (Salmoni, Schmidt, & Walter, 1984). Some studies in the past few years have compared the effectiveness of knowledge of results feedback (KR) after relatively more accurate versus less accurate trials on motor learning (Abbas & North, 2018;Badami, VaezMousavi, Wulf, & Namazizadeh, 2012;Chiviacowsky & Wulf, 2007;Chiviacowsky, Wulf, Wally, & Borges, 2009;Goudini, Saemi, Ashrafpoornavaee, & Abdoli, 2018;Januário, Figueiredo, Portes, & Benda, 2019;Saemi, Porter, Ghotbi-Varzaneh, Zarghami, & Maleki, 2012;Saemi, Wulf, Varzaneh, & Zarghami, 2011). In these studies, KR feedback was provided after each block of practice trials.…”
Section: Introductionmentioning
confidence: 99%
“…Less controversially, there are reports that participants perform better when they are told they are doing well (Saemi et al, 2011;Trempe et al, 2012), when they are informed that peers do well on the current task (Wulf et al, 2012), and in accordance with superstitious beliefs (Damisch et al, 2010). As part of their OPTIMAL (Optimizing Performance through Intrinsic Motivation and Attention for Learning) framework, Wulf and Lewthwaite (2016) explain the relationship between perception and performance as at least partly related to attentional allocation.…”
Section: Ebbinghaus Illusion and Actions At A Distancementioning
confidence: 99%